Pendampingan Dasar Autodesk Inventor dan 3D Printing Untuk Penguatan Keterampilan Siswa Kelas XI Teknik Kendaraan Ringan SMK Muhammadiyah Larangan Brebes - Sigit Setijo Budi; Andre Budhi Hendrawan (Jurnal Masyarakat Indonesia (Jumas), 2025)
Digital technology-based design and fabrication skills are essential for Vocational High School students, particularly in the Light Vehicle Engineering competency. Initial identification results indicate that 11th-grade students of Muhammadiyah Larangan Brebes Vocational High School do not yet have adequate experience in three-dimensional modeling and the use of 3D printing technology. This community service activity aims to provide basic assistance in the use of Autodesk Inventor and 3D printing as an effort to strengthen students' technical skills. The implementation of the activity is carried out through the delivery of introductory material, simple component modeling practice using Autodesk Inventor, an introduction to the working principles and materials of 3D printing, and assistance in the printing process of designed objects. Evaluation is carried out by comparing students' initial and final abilities and observing practical skills during the activity. The results of the activity show an increase in students' understanding of 3D design concepts, the ability to create simple component models, and basic knowledge of the three-dimensional printing process. This activity has a positive impact on improving student competencies and can support the readiness of vocational high school graduates in facing developments in manufacturing technology.